Nominal Affixing In The Kainji Languages Of Northwestern And Central Nigeria - Blench, Roger (My University, 2018)
The Kainji languages of northwest and central Nigeria remain little-researched and sparsely described. Their nominal morphology strongly resembles Bantu typologically, but finding segmental cognates remains problematic. They show systems of alternating prefixes and alliterative concord, as well as diminutive and augmentative prefixes and CV- prefixes with underspecified vowels, where the -V of the prefix harmonises with the stem vowel. The limited segmental cognates point to radical restructuring through affix loss and renewal. Indeed one language, Shen, has lost all nominal morphology and it is severely reduced in some branches. Reshe is typologically similar to other Kainji languages, but the affixes seem to have been completely restructured. The paper presents an overview of the literature on Kainji and then describes the nominal affixing in individual branches. It concludes by suggesting what hypotheses can be made about the Kainji system as a whole.
Keywords: Historical linguistics; Kainji languages; noun classes; Niger-Congo